The impact of chatbots on EFL students’ English reading comprehension - Nhan Nguyen Thanh Dinh; Hung Minh Do; Quy Thi Kim Tran (Ho Chi Minh City Open University Journal of Science - Social Sciences)
The advent of Chatbots as potential tools for learning English has provided EFL students with opportunities for interactive English practice and enhanced research skills using open-access sources, offering employment opportunities for college graduates. However, the practical benefits of language learning in Vietnamese higher education institutions need more in-depth research. This study, therefore, was conducted with 45 second-year EFL students at Ho Chi Minh City University in Vietnam, whose English proficiency level was equivalent to B1. It investigates the empirical effectiveness of Chatbots in acquiring English language skills, focusing specifically on reading comprehension, critical thinking, and creativity. Addressing two key questions, namely, the impact on students’ reading comprehension, learner autonomy, and perceptions of Chatbots for enhancing comprehension, the study incorporates an 8-week Chatbot-integrated classroom intervention program. Data were collected through surveys and interviews, then compared and contrasted to measure reading comprehension and learner autonomy improvement. Findings indicate that Chatbots significantly enhance reading comprehension, foster learner autonomy, and stimulate critical thinking. The research offers a comprehensive overview of Chatbots in EFL, recognizing associated limitations, and advocates for further exploration of A.I.-linked EFL education, exploring advantages and limitations, especially regarding learners’ academic achievement and well-being, as a burgeoning trend in Vietnam and globally.